Nanovector Delivery of siRNA for Cancer Therapy - Ferrari, Mauro (2012)
RNA interference holds the promise to knock down expression of every cancer gene. Both academic laboratories and pharmaceutical companies have committed heavily on manpower and financial resources to develop siRNA cancer therapeutics over the last decade. While significant advances have been made in the design of siRNA therapeutics and mechanism of action on cancer cell killing, there are still many hurdles to overcome including effective delivery of therapeutics in vivo. Nanotechnology has played an important role in the development of delivery vectors so far. This article summarizes current nanovectors for siRNA delivery, discusses technical challenges in overcoming biological barriers, and introduces the multistage vector system for tumor-specific delivery.